2020
DOI: 10.48550/arxiv.2005.11479
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

No pulsed radio emission during a bursting phase of a Galactic magnetar

L. Lin,
C. F. Zhang,
P. Wang
et al.

Abstract: Fast radio bursts (FRBs) are mysterious millisecond-duration radio transients observed from extragalactic distances [1][2][3] . Magnetars have been long speculated as the possible engine to power repeating bursts from FRB sources [4][5][6][7][8][9][10][11][12][13] , but no convincing evidence has been collected so far 14 . Recently, a Galactic magnetar dubbed Soft Gamma-ray Repeater (SGR) J1935+2154 entered an active phase by emitting intense soft gamma-ray bursts 15 . One fast radio burst with two peaks (here… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 30 publications
(59 reference statements)
3
29
1
Order By: Relevance
“…3). SGR 1935 has a high rotational power, but so far it did not show any radio pulsations (Younes et al 2017b;Lin et al 2020b), while surprisingly emitting radio bursts during the outburst we report here. From the study of the bursting activity of this source, it becomes clear that: 1) not all X-ray magnetar bursts have necessarily a radio counterpart (see also Archibald et al 2020), and 2) many radio bursts from magnetars might have been missed due to the lack of large field-of-view instruments in the radio band.…”
contrasting
confidence: 49%
See 1 more Smart Citation
“…3). SGR 1935 has a high rotational power, but so far it did not show any radio pulsations (Younes et al 2017b;Lin et al 2020b), while surprisingly emitting radio bursts during the outburst we report here. From the study of the bursting activity of this source, it becomes clear that: 1) not all X-ray magnetar bursts have necessarily a radio counterpart (see also Archibald et al 2020), and 2) many radio bursts from magnetars might have been missed due to the lack of large field-of-view instruments in the radio band.…”
contrasting
confidence: 49%
“…More interestingly, two millisecond radio bursts temporally coincident with a double-peaked hard X-ray burst were detected from the direction of the source (The CHIME/FRB Collaboration et al 2020;Bochenek et al 2020;Li et al 2020;Mereghetti et al 2020;Tavani et al 2020), strenghtening the long suspected connection between magnetars and fast radio bursts (FRBs; see Cordes & Chatterjee 2019;Petroff et al 2019 for reviews). However, besides these radio bursts, radio pulsed emission has not been detected so far from the source (e.g., Younes et al 2017b;Lin et al 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…Any explanation of FRB as products of SGR must be consistent with "cosmological" FRB whose radio emission is several orders of magnitude more energetic than that of FRB 200428 and with the radio-to-gamma ray fluence ratio of FRB 200428 more than five orders of magnitude greater than that of SGR 1806−20. A number of theoretical interpretations have been suggested (Lu, Kumar & Zhang 2020;Lyutikov & Popov 2020;Margalit et al 2020;Wang, Xu & Chen 2020).…”
Section: Frbmentioning
confidence: 99%
“…Although FRB 200428 was found to be associated with a hard X-ray burst, deep searches by Five-hundredmeter Aperture Spherical Telescope (FAST) for FRBs revealed no single detection, even during the epochs when 29 soft-γ-ray bursts were detected by Fermi GBM (Lin et al 2020). This suggests that the FRB-SGR association is very rare.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the FRB-SGR association is very rare. Among other possibilities, the low probability of association could be due to the narrow spectra of FRBs (Lin et al 2020). Such narrow spectra have been hinted by the extreme variation of spectral indices among different bursts of FRB 121102 (Spitler et al 2016) as well as the relative fluence of the two peaks of FRB 200428 as observed by CHIME and STARE2.…”
Section: Introductionmentioning
confidence: 99%